Registration of functional deviations cell system eritron method of computer morphometry - Tatiana Petrovna Bondar; Oksana Ivanovna Anfinogenova (Наука. Инновации. Технологии, 2022)
In the course of the study there are some functional changes in the red blood cells in healthy young men, students at the university in the first year. Our results with respect to changes in the shape and size of the erythrocyte, showing a decrease in the area of the cell and its diameter exhibit a certain tension in the system of red blood.